Concrete formula, preparation method and concrete regeneration process thereof

By using nanosilica solution to repair the internal structure of waste concrete in the traditional concrete regeneration process, and adding fibers and nanosilica to the concrete formula, the problem of insufficient strength and crack resistance in the traditional concrete regeneration process is solved, and higher density and strength are achieved.

CN119591358AInactive Publication Date: 2025-03-11FOSHAN SHUNDE HELE COMMERCIAL CONCRETE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411564993.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In traditional concrete regeneration technology, the crushed concrete has poor strength and poor crack resistance, which cannot meet the construction needs.

Method used

Used by soaking the discarded concrete in a nanosilicon dioxide solution to repair the internal structure and crushing it into two different aggregates. During the mixing process of silicate cement, natural aggregate and other materials, polypropylene fiber and glass fiber are added in batches to enhance crack resistance through fiber additives, and micropores in the concrete are filled with nanosilica.

Benefits of technology

The density, strength and crack resistance of concrete are improved, making it more dense and stronger, and the strength of regenerated aggregates are better, and the mixing reaction with cement is better.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005119996810000111
    Figure BDA0005119996810000111
Patent Text Reader

Abstract

The invention relates to the field of concrete preparation, in particular to a concrete formula, a preparation method and a concrete regeneration process. Portland cement, aggregate, gravel, a fiber additive and nano silicon dioxide are selected as main materials to be stirred and mixed; and continuously soaking in a nano silicon dioxide solution to improve the overall strength of the aggregate. According to the invention, the internal structure of the crushed waste concrete is repaired in a manner of soaking the crushed waste concrete in a nano silicon dioxide solution, the crushed waste concrete is crushed into two different aggregates for use, and polypropylene fibers and glass fibers are added in batches in the mixing process of materials such as Portland cement and natural aggregates. The fiber additive is added to enhance the crack resistance of the concrete, micropores in the concrete are filled with the nano silicon dioxide, the compactness and crack resistance of the concrete are improved, the prepared concrete is higher in density and better in strength, and the strength of the recycled aggregate is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete preparation, and in particular to a concrete formula and preparation method and a concrete regeneration process. Background Art

[0002] As the most widely used man-made building material, concrete plays an important role in construction projects. Every year, a large amount of waste concrete is demolished and waste concrete is generated from new buildings. The traditional way of dealing with it is to crush the large amount of waste concrete and add corresponding materials to re-make concrete.

[0003] However, in the traditional concrete recycling process, waste concrete is usually crushed and put into use after proper treatment by adding additives and aggregates. In actual use, the internal structure of the crushed concrete is destroyed and changed, making the concrete produced by this process have poor strength and crack resistance, which cannot meet the needs of construction use. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a concrete formula and a preparation method and a concrete regeneration process.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A concrete formula, in parts by mass, comprising:

[0007] 100-150 parts of Portland cement, 400-500 parts of aggregate, 250-350 parts of sand and gravel, 100-150 parts of raw water, 10-30 parts of polymer modifier, 10-50 parts of fiber additive, 10-20 parts of expansion agent, 10-20 parts of admixture, 5-11 parts of talc, 30-50 parts of nano silicon dioxide;

[0008] Based on the above-mentioned formula raw materials, a method for preparing a concrete formula includes the following steps:

[0009] S1. Select natural aggregates, including sand and pebbles with a particle size of 0.6-0.8 mm, and select recycled aggregates with a particle size of 1.3-1.5 mm, mix the two and set aside;

[0010] S2, adding talcum powder and coarse sand and gravel with a particle size of 2.0-2.6 mm into the mixing equipment, and simultaneously adding the aggregate mixed in S1, and stirring at a uniform speed for 2-3 hours at a mixing chamber temperature of 55-65°C;

[0011] S3, taking out the aggregate mixture prepared in S2, and sieving fine dust through a 40-mesh sieve, and naturally standing and cooling to room temperature;

[0012] S4. After cooling, the aggregate mixture is loaded into a container, and a quantitative amount of silicate cement, sand, raw water, expansion agent, admixture, and nano-silicon dioxide are added simultaneously, stirred several times to completely mix, and then allowed to stand for 3-5 hours to obtain a mixture A;

[0013] S5. Heat the mixture A to 60-70° C. and stir it at a speed of 200-300 rpm for 0.5-0.9 h during the heating process. Simultaneously add the fiber additive to the mixture A, and simultaneously add a certain amount of talcum powder and a polymer modifier and continue stirring to obtain the mixture.

[0014] Preferably, the aggregate includes natural aggregate and recycled aggregate, wherein the natural aggregate is specifically gravel and pebbles, wherein the mass percentage of pebbles to gravel is 3:(2-3).

[0015] Preferably, the mass ratio of the natural aggregate to the recycled aggregate is (1-1.6):(2-3).

[0016] Preferably, the fiber additive includes polypropylene fiber and glass fiber, wherein the mass ratio of the polypropylene fiber to the glass fiber is (1-1.2):(1.2-1.4).

[0017] Preferably, the amount of the expansion agent added does not exceed 5-7% of the amount of silicate cement used.

[0018] Preferably, during the stirring and mixing of the fiber additives in S5, glass fibers are preferentially added for mixing, and when the fibers are evenly mixed and distributed in the A mixture, polypropylene fibers are simultaneously added for stirring and mixing.

[0019] Preferably, the raw water is added in batches, and the percentage of each addition is 0.3:0.5:(0.2-0.3), and the corresponding consistency and fluidity of the concrete are observed.

[0020] Preferably, the admixture includes a retarder, and the amount added does not exceed 2-3% of the total amount of silicate cement.

[0021] A concrete recycling process comprises the following steps:

[0022] A. Obtain waste concrete and crush it to remove the steel bars, debris and impurities inside it, and put it into water for preliminary stirring and cleaning, and then take out the cleaned concrete fragments and dry them naturally;

[0023] B. Then, the concrete fragments are placed in a nano-silicon dioxide solution and soaked at room temperature for 48-56 hours;

[0024] C. After the belt is soaked, the concrete fragments are crushed to obtain blocks with a size of less than 3.5x3.5mm, and then the impurities and dust on the surface of the fragments are washed off and immersed in the nano-silicon dioxide solution in B again for 48-56h;

[0025] D. The fragments obtained in C are completely dried and ground to a particle size of 1.3-1.5 mm by a grinder, and then general aggregates are taken for secondary crushing to a particle size of 0.3-0.7 mm.

[0026] The beneficial effects of the present invention are:

[0027] In the present invention, the internal structure of the crushed waste concrete is repaired by soaking it in a nano-silicon dioxide solution, and the crushed concrete is used as two different aggregates. In the mixing process of materials such as silicate cement and natural aggregate, polypropylene fiber and glass fiber are added in batches. The fiber additive is added to enhance the crack resistance of the concrete, and nano-silicon dioxide is used to fill the micropores in the concrete, thereby improving the compactness and crack resistance of the concrete. Compared with the traditional process, the concrete prepared by the method has higher density and better strength, and the strength of the recycled aggregate is better, and the mixing reaction with cement is better. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0029] Example 1

[0030] A concrete formula, in parts by mass, comprising:

[0031] 100 parts of Portland cement, 400 parts of aggregate, 250 parts of sand and gravel, 100 parts of raw water, 10 parts of polymer modifier, 10 parts of fiber additive, 10 parts of expansion agent, 10 parts of admixture, 5 parts of talc, 30 parts of nano silicon dioxide;

[0032] Based on the above-mentioned formula raw materials, a method for preparing a concrete formula includes the following steps:

[0033] S1. Select natural aggregates, including sand and pebbles with a particle size of 0.6 mm, and select recycled aggregates with a particle size of 1.3 mm, mix the two and set aside;

[0034] S2, adding talcum powder and coarse sand and gravel with a particle size of 2.0 mm into the mixing equipment, and simultaneously adding the aggregate mixed in S1, and stirring at a uniform speed for 2 hours at a mixing chamber temperature of 55°C;

[0035] S3, taking out the aggregate mixture prepared in S2, and sieving fine dust through a 40-mesh sieve, and naturally standing and cooling to room temperature;

[0036] S4. After cooling, the aggregate mixture is loaded into a container, and a quantitative amount of silicate cement, sand, raw water, expansion agent, admixture, and nano-silicon dioxide are added simultaneously, stirred several times to completely mix, and then allowed to stand for 3 hours to obtain a mixture A;

[0037] S5. Heat the mixture A to 60° C. and stir it at a constant speed of 200 rpm for 0.5 h during the heating process. Simultaneously, add the fiber additive to the mixture A, and simultaneously add a certain amount of talcum powder and a polymer modifier and continue stirring to obtain the mixture.

[0038] A concrete recycling process comprises the following steps:

[0039] A. Obtain waste concrete and crush it to remove the steel bars, debris and impurities inside it, and put it into water for preliminary stirring and cleaning, and then take out the cleaned concrete fragments and dry them naturally;

[0040] B. Then, the concrete fragments were placed in a nano-silicon dioxide solution and soaked at room temperature for 48 hours;

[0041] C. After the belt is soaked, the concrete fragments are crushed to obtain blocks with a size of less than 3.5x3.5mm, and then the impurities and dust on the surface of the fragments are washed off and immersed in the nano-silicon dioxide solution in B for 48 hours;

[0042] D. The fragments obtained in C are completely dried and ground to a particle size of 1.3 mm using a grinder, and then general aggregates are used for secondary crushing to a particle size of 0.3 mm.

[0043] Furthermore, the aggregate includes natural aggregate and recycled aggregate, wherein the natural aggregate is specifically gravel and pebbles, wherein the mass percentage of pebbles to gravel is 3:2.

[0044] Furthermore, the mass ratio of natural aggregate to recycled aggregate is specifically 1:2.

[0045] Furthermore, the fiber additive includes polypropylene fiber and glass fiber, wherein the mass ratio of the polypropylene fiber to the glass fiber is 1:1.2.

[0046] Furthermore, the amount of expansion agent added does not exceed 5% of the amount of silicate cement used.

[0047] Furthermore, during the stirring and mixing process of the fiber additives in S5, glass fibers are preferentially added for mixing, and when the fibers are evenly mixed and distributed in the A mixture, polypropylene fibers are simultaneously added for stirring and mixing.

[0048] Furthermore, the raw water is added in batches, and the percentage of each addition is 0.3:0.5:0.2, and the corresponding consistency and fluidity of the concrete are observed.

[0049] Furthermore, the admixture includes a retarder, and the amount of the retarder added does not exceed 2% of the total amount of silicate cement.

[0050] Example 2

[0051] A concrete formula, in parts by mass, comprising:

[0052] 125 parts of Portland cement, 450 parts of aggregate, 300 parts of sand and gravel, 125 parts of raw water, 20 parts of polymer modifier, 30 parts of fiber additive, 15 parts of expansion agent, 15 parts of admixture, 8 parts of talc, 40 parts of nano silicon dioxide;

[0053] Based on the above-mentioned formula raw materials, a method for preparing a concrete formula includes the following steps:

[0054] S1. Select natural aggregates, including sand and pebbles with a particle size of 0.7 mm, and select recycled aggregates with a particle size of 1.4 mm, mix the two and set aside;

[0055] S2, adding talcum powder and coarse sand and gravel with a particle size of 2.3 mm into the mixing equipment, and simultaneously adding the aggregate mixed in S1, and stirring at a uniform speed for 2.5 hours at a mixing chamber temperature of 60°C;

[0056] S3, taking out the aggregate mixture prepared in S2, and sieving fine dust through a 40-mesh sieve, and naturally standing and cooling to room temperature;

[0057] S4, after cooling, the aggregate mixture is loaded into a container, and a quantitative amount of silicate cement, sand, raw water, expansion agent, admixture, and nano-silicon dioxide are added simultaneously, stirred several times to completely mix, and then allowed to stand for 4 hours to obtain a mixture A;

[0058] S5. Heat the A mixture to 65° C. and stir it at a constant speed of 250 rpm for 0.7 h during the heating process. Simultaneously, add the fiber additive to the A mixture, and simultaneously add a certain amount of talcum powder and a polymer modifier and continue stirring to obtain the mixture.

[0059] A concrete recycling process comprises the following steps:

[0060] A. Obtain waste concrete and crush it to remove the steel bars, debris and impurities inside it, and put it into water for preliminary stirring and cleaning, and then take out the cleaned concrete fragments and dry them naturally;

[0061] B. Then, the concrete fragments were placed in a nano-silicon dioxide solution and soaked at room temperature for 52 hours;

[0062] C. After the belt is soaked, the concrete fragments are crushed to obtain blocks with a size of less than 3.5x3.5mm, and then the impurities and dust on the surface of the fragments are washed off and immersed in the nano-silicon dioxide solution in B for 52h again;

[0063] D. The fragments obtained in C are completely dried and ground to a particle size of 1.4 mm using a grinder, and then general aggregates are used for secondary crushing to a particle size of 0.5 mm.

[0064] Furthermore, the aggregate includes natural aggregate and recycled aggregate, wherein the natural aggregate is specifically gravel and pebbles, wherein the mass percentage of pebbles to gravel is 3:2.5.

[0065] Furthermore, the mass ratio of natural aggregate to recycled aggregate is specifically 1.3:2.5.

[0066] Furthermore, the fiber additive includes polypropylene fiber and glass fiber, wherein the mass ratio of the polypropylene fiber to the glass fiber is 1.1:1.3.

[0067] Furthermore, the amount of expansion agent added does not exceed 6% of the amount of silicate cement used.

[0068] Furthermore, during the stirring and mixing process of the fiber additives in S5, glass fibers are preferentially added for mixing, and when the fibers are evenly mixed and distributed in the A mixture, polypropylene fibers are simultaneously added for stirring and mixing.

[0069] Furthermore, the raw water is added in batches, and the percentage of each addition is 0.3:0.5:0.25, and the corresponding consistency and fluidity of the concrete are observed.

[0070] Furthermore, the admixture includes a retarder, and the amount of the retarder added does not exceed 2-3% of the total amount of silicate cement.

[0071] Example 3

[0072] A concrete formula, in parts by mass, comprising:

[0073] 150 parts of Portland cement, 500 parts of aggregate, 350 parts of sand and gravel, 150 parts of raw water, 30 parts of polymer modifier, 50 parts of fiber additive, 20 parts of expansion agent, 20 parts of admixture, 11 parts of talc, 50 parts of nano silicon dioxide;

[0074] Based on the above-mentioned formula raw materials, a method for preparing a concrete formula includes the following steps:

[0075] S1. Select natural aggregates, including sand and pebbles with a particle size of 0.8 mm, and select recycled aggregates with a particle size of 1.5 mm, mix the two and set aside;

[0076] S2, adding talcum powder and coarse sand and gravel with a particle size of 2.6 mm into the mixing equipment, and simultaneously adding the aggregate mixed in S1, and stirring at a constant speed for 3 hours at a mixing chamber temperature of 65°C;

[0077] S3, taking out the aggregate mixture prepared in S2, and sieving fine dust through a 40-mesh sieve, and naturally cooling it to room temperature;

[0078] S4. After cooling, the aggregate mixture is loaded into a container, and a quantitative amount of silicate cement, sand, raw water, expansion agent, admixture, and nano-silicon dioxide are added simultaneously, stirred several times to completely mix, and then allowed to stand for 5 hours to obtain a mixture A;

[0079] S5. Heat the mixture A to 70° C. and stir it at a constant speed of 300 rpm for 0.9 h during the heating process. Simultaneously, add the fiber additive to the mixture A, and simultaneously add a certain amount of talcum powder and a polymer modifier and continue stirring to obtain the mixture.

[0080] A concrete recycling process comprises the following steps:

[0081] A. Obtain waste concrete and crush it to remove the steel bars, debris and impurities inside it, and put it into water for preliminary stirring and cleaning, and then take out the cleaned concrete fragments and dry them naturally;

[0082] B. Then, the concrete fragments were placed in a nano-silicon dioxide solution and soaked at room temperature for 56 hours;

[0083] C. After the belt is soaked, the concrete fragments are crushed to obtain blocks with a size of less than 3.5x3.5mm, and then the impurities and dust on the surface of the fragments are washed off and immersed in the nano-silicon dioxide solution in B for 56 hours;

[0084] D. The fragments obtained in C are completely dried and ground to a particle size of 1.5 mm using a grinder, and then general aggregates are taken for secondary crushing to a particle size of 0.7 mm.

[0085] Furthermore, the aggregate includes natural aggregate and recycled aggregate, wherein the natural aggregate is specifically gravel and pebbles, wherein the mass percentage of pebbles to gravel is 3:3.

[0086] Furthermore, the mass ratio of natural aggregate to recycled aggregate is specifically 1.6:3.

[0087] Furthermore, the fiber additive includes polypropylene fiber and glass fiber, wherein the mass ratio of the polypropylene fiber to the glass fiber is 1.2:1.4.

[0088] Furthermore, the amount of expansion agent added does not exceed 7% of the amount of silicate cement used.

[0089] Furthermore, during the stirring and mixing process of the fiber additives in S5, glass fibers are preferentially added for mixing, and when the fibers are evenly mixed and distributed in the A mixture, polypropylene fibers are simultaneously added for stirring and mixing.

[0090] Furthermore, the raw water is added in batches, and the percentage of each addition is 0.3:0.5:0.3, and the corresponding consistency and fluidity of the concrete are observed.

[0091] Furthermore, the admixture includes a retarder, and the amount of the retarder added does not exceed 3% of the total amount of silicate cement.

[0092] In this embodiment, the waste concrete is crushed to remove impurities such as steel bars and debris inside it, and is put into water for preliminary stirring, cleaning and airing. After the surface of the belt is completely dry, the concrete block is immersed in a nano-silicon dioxide solution, and after the first round of immersion, it is taken out for secondary crushing, and then immersed again to improve the overall strength of the concrete block, and the internal structure of the waste concrete is repaired and improved to form a tighter structure, thereby forming recycled aggregate.

[0093] Then, the prepared recycled aggregate is mixed with natural aggregate to form aggregate, and is mixed with silicate cement, sand and gravel, raw water, polymer modifier, fiber additive, expansion agent, admixture, talcum powder and nano-silicon dioxide. Fiber additives are added in batches during the mixing process, mainly polypropylene fiber and glass fiber, to further improve the crack resistance of concrete. At the same time, the added nano-silicon dioxide can effectively fill the micropores in the concrete, thereby improving the density and crack resistance of the concrete.

[0094] Among them, ordinary cement concrete was taken as sample A, silicate cement concrete was taken as sample B, fly ash cement concrete was taken as sample C, slag silicate cement concrete was taken as sample D, and fiber-containing silicate cement concrete was taken as sample E, and crack resistance tests were conducted, and the following table was obtained:

[0095]

[0096] In the present invention, the internal structure of the crushed waste concrete is repaired by soaking it in a nano-silicon dioxide solution, and the crushed concrete is used as two different aggregates. In the mixing process of materials such as silicate cement and natural aggregate, polypropylene fiber and glass fiber are added in batches. The fiber additive is added to enhance the crack resistance of the concrete, and nano-silicon dioxide is used to fill the micropores in the concrete, thereby improving the compactness and crack resistance of the concrete. Compared with the traditional process, the concrete prepared by the method has higher density and better strength, and the strength of the recycled aggregate is better, and the mixing reaction with cement is better.

[0097] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A concrete formula, characterized in that: In parts by mass, the formula comprises: 100-150 parts of Portland cement, 400-500 parts of aggregate, 250-350 parts of sand and gravel, 100-150 parts of raw water, 10-30 parts of polymer modifier, 10-50 parts of fiber additive, 10-20 parts of expansion agent, 10-20 parts of admixture, 5-11 parts of talc, 30-50 parts of nano silicon dioxide; Based on the above-mentioned formula raw materials, a method for preparing a concrete formula includes the following steps: S1. Select natural aggregates, including sand and pebbles with a particle size of 0.6-0.8 mm, and select recycled aggregates with a particle size of 1.3-1.5 mm, mix the two and set aside; S2, adding talcum powder and coarse sand and gravel with a particle size of 2.0-2.6 mm into the mixing equipment, and simultaneously adding the aggregate mixed in S1, and stirring at a uniform speed for 2-3 hours at a mixing chamber temperature of 55-65°C; S3, taking out the aggregate mixture prepared in S2, and sieving fine dust through a 40-mesh sieve, and naturally standing and cooling to room temperature; S4. After cooling, the aggregate mixture is loaded into a container, and a quantitative amount of silicate cement, sand, raw water, expansion agent, admixture, and nano-silicon dioxide are added simultaneously, stirred several times to completely mix, and then allowed to stand for 3-5 hours to obtain a mixture A; S5. Heat the mixture A to 60-70° C. and stir it at a speed of 200-300 rpm for 0.5-0.9 h during the heating process. Simultaneously add the fiber additive to the mixture A, and simultaneously add a certain amount of talcum powder and a polymer modifier and continue stirring to obtain the mixture.

2. The method for preparing a concrete formula according to claim 1, characterized in that: The aggregate includes natural aggregate and recycled aggregate, wherein the natural aggregate is specifically gravel and pebbles, wherein the mass percentage of pebbles to gravel is 3:(2-3).

3. The method for preparing a concrete formula according to claim 2, characterized in that: The mass ratio of the natural aggregate to the recycled aggregate is specifically (1-1.6):(2-3).

4. The method for preparing a concrete formula according to claim 1, characterized in that: The fiber additives include polypropylene fibers and glass fibers, wherein the mass ratio of the polypropylene fibers to the glass fibers is (1-1.2):(1.2-1.4).

5. The method for preparing a concrete formula according to claim 1, characterized in that: The amount of the expansion agent added does not exceed 5-7% of the amount of silicate cement used.

6. The method for preparing a concrete formula according to claim 1, characterized in that: In the stirring and mixing process of the fiber additives in S5, glass fibers are added first for mixing, and when the fibers are evenly mixed and distributed in the mixture A, polypropylene fibers are simultaneously added for stirring and mixing.

7. The method for preparing a concrete formula according to claim 1, characterized in that: The raw water is added in batches, and the percentage of each addition is 0.3:0.5:(0.2-0.3), and the corresponding consistency and fluidity of the concrete are observed.

8. The method for preparing a concrete formula according to claim 1, characterized in that: The admixture includes a retarder, and the amount of the retarder added does not exceed 2-3% of the total amount of silicate cement.

9. A concrete regeneration process according to any one of claims 1 to 8, characterized in that: The following steps are involved: A. Obtain waste concrete and crush it to remove the steel bars, debris and impurities inside it, and put it into water for preliminary stirring and cleaning, and then take out the cleaned concrete fragments and dry them naturally; B. Then, the concrete fragments are placed in a nano-silicon dioxide solution and soaked at room temperature for 48-56 hours; C. After the belt is soaked, the concrete fragments are crushed to obtain blocks with a size of less than 3.5x3.5mm, and then the impurities and dust on the surface of the fragments are washed off and immersed in the nano-silicon dioxide solution in B for 48-56h again; D. The fragments obtained in C are completely dried and ground to a particle size of 1.3-1.5 mm by a grinder, and then general aggregates are taken for secondary crushing to a particle size of 0.3-0.7 mm.

Citation Information

Patent Citations

  • Reinforced recycled concrete and production process thereof

    CN113105181A

  • Recycled concrete capable of reducing porosity and preparation method thereof

    CN114230281A